Rapid diagnosis of the most common causes of abortion in Awassi ewes in Nineveh Governorate, Iraq (NTU Journal of Agriculture and Veterinary Science, 2024)
The study aimed to determine the rates of infection with the most common causes of abortion by Rapid methods of diagnosis, and abortion rates in the governorate’s areas. Rapid methods of diagnosis are important to help the veterinarian in diagnosing abortions in order to reduce the economic loss of sheep by taking the appropriate decision and treatment within a short time. This study was conducted on 92 samples (46 vaginal swabs, 46 blood) representing 60 flocks, the study was conducted from August 2022 to January 2023. The following tests were used, FASTest CHLAM Ag rapid screening test for Chlamydia, Rose Bengal Agglutination Test for Brucella, and Latex agglutination test for Toxoplasma. Results indicate that 13/46 positive samples were 28.26% for chlamydia, 29/46 positive samples 63.04% for Brucella, and 17/46 positive samples 36.95% for toxoplasma. It has been concluded that with a high infection rate of Chlamydia abortus in ewes in Nineveh, the rapid test was ideal for the diagnosis of Chlamydia. A high infection rate of Chlamydia in the center and northern areas of Nineveh.